Wuo Yuan Yi: kei nien ching tu che: chen fu shih li hua te yi sheng - Cárceles, Miguel Ángel; Torra, Isabel; Del Lungo, Giorgio (First Town)
Semblanza escrita para niños, con ilustraciones de Giorgio del Lungo
Keywords: Vida